Epidemiological profile of indigenous cancer patients : a retrospective study from a comprehensive Cancer Care Centre in Northern Kerala, India during the period 2016 to 2020 - Lakshya Ramadas Krishnaprasad (2025)
Background and Aims: Cancer is a significant health issue for Indigenous populations worldwide as it is one of the leading causes of illness and death. India has the second largest Indigenous population in the world, however there is a paucity of studies focusing specifically on the cancer epidemiology and treatment adherence among Indigenous population in the country. Thus, the aim of this study is to investigate the epidemiological profile and adherence to the treatment and followup instructions among them. Materials and Methods: A retrospective study was conducted in a comprehensive cancer care centre in Northern Kerala, India, during the period of 2016 to 2020. The data collection sheets were used to extract the data from the medical records. Results: A total of 511 Indigenous cancer patients were included in the study with a mean age of 54.53 ±13.67 years. Among them 52% were males and 48% were females. The majority of the population (54%) were illiterate and 74% belonged to low socio-economic group. Fifty-nine percentage of the population had smokeless tobacco consumption. The leading cancer sites were Ca lip and oral cavity (34%), Ca lung (8.41%) and Ca breast (6.84%). Seventy percentage of the patients were diagnosed at advanced TNM stages and 47% were planned for palliative treatment. Majority (86%) followed their treatment plans, and 62% were in active follow-up. Conclusion: Several socio-economic factors, including high illiteracy rates, low socio-economic status, significant unemployment, and rural residency, create a complex barrier that adversely affects cancer outcomes for this group. Notably, tobacco consumption was high among both men and women, leading to an incidence of Tobacco Related Cancers (TRC). Most cancer cases were diagnosed at an advanced stage, resulting in many patients requiring palliative care. Addressing the modifiable risk factors like tobacco use among the Indigenous population, encouraging early detection, enhancing health literacy, and improving health-seeking behavior can significantly reduce the cancer burden among them. Further extensive research is needed for cancer prevention and control among them.
Keywords: Cancer; Epidemiological profile; Treatment adherence; Indigenous population